Effect of the growth time on the content of inulin, polyphenol, flavonoids, total sugar, minerals, and antioxidant activity of Vietnamese Dangshen roots (Codonopsis javanica). - Nguyễn, Thị Thăng Long (2022)
Vietnamese dangshen (Codonopsis javanica) grows naturally at an altitude of 800m in Lam Dong province, Vietnam in comparison to seawater is as a bioactive rich-medicine plant. The content of inulin, polyphenol, flavonoids, total sugar, and mineral, and antioxidant activity (TAC, FRAP, and ABTS) of them according to the growth time (1st, 2nd, 3rd and 4th years) was showed in the paper. Vietnamese dangshen was sliced thin, and dried at the temperature of 55 ± 0.1°C until the humidity of (8 ± 1)% for further study. The growth time of dangshen affected the content of inulin, polyphenol, flavonoids, total sugar, and mineral, and antioxidant activity of Vietnamese dangshen roots. Total sugar content (16.48a ± 1.45)%, and inulin content (222.24±3.54 mg fructose equivalent/g DW), polyphenol content (1.39a ± 0.055 mg gallic acid equivalent/g DW), flavonoids content (0.87a±0.007 mg quercetin equivalent/g DW), and antioxidant activity (23.64a±0.57 mg ascorbic acid equivalent/g DW), ABTS (15.65a±1.98)%, and FRAP (15.39a±0.53 mg FeSO4 equivalent/ g DW) got the highest value in the period of 1st year and 3rd year, respectively; highest mineral content (3.33 ± 0.36)% was in the period of 4th year. The results will be good science basics for harvesting, processing, and using Vietnamese dangshen (Codonopsis javanica) into function foods, pharmaceutics.